Biotechnological potential of the yeast Kluyveromyces marxianus - Viana, Nádia Cristina (2022)
Alcoholic fermentation on an industrial scale for ethanol production from sugarcane remains a challenge to maintain the best yield and cost-benefit ratio. Despite advances, more recent industrial applications, such as bioethanol production at high sugar concentrations and at high temperatures, demand further studies on yeast metabolism. There is the motivation for the study of the biotechnological applications of unconventional yeasts, such as the yeast Kluyveromyces marxianus, which stands out for presenting high tolerance to high temperatures and accelerated cell growth capacity in these conditions, including the facility to growing on a larger number of substrates and with an efficient and fast metabolism. In order to evaluate the biotechnological potential of K. marxianus, determining its fermentative profile and its response to stressors, sugar consumption and growth, the strains IZ 1339 (isolated from Drosophila) and FT 146L (isolated from bioprocesses) were used. The growth characteristics in microplate, consumption of sugars in single carbon source (glucose, sucrose, xylose, lactose and maltose) and binary mixtures (glu/xyl, glu/lac, suc/lac and mal/lac), as well as the growth profile under stress sources (saline, ethanol and acid) were explored, with growth curves and kinetic parameters obtained. Then, the kinetic profile of both K. marxianus strains was evaluated in a non- invasive sampling system, comparing their growth profiles, including the specific maximum velocity, and their performance in sugarcane juice medium. Finally, fermentation assays were carried out on a shaker scale with inoculum recycling, and in a bioreactor. The fermentation and yield parameters were evaluated, providing data such as sugar consumption and ethanol production. Therefore, it is possible to conclude that Kluyveromyces marxianus has positive characteristics for industrial application in substrates commonly used in Brazil, such as sugarcane juice and molasses.